Correlations between problematic internet use and suicidal behavior among Chinese adolescents: a systematic review and meta-analysis - He, Xubin; Chen, Si; Yu, Qinyao; Yang, Ping; Yang, Bo (Frontiers in Psychiatry, 2024)
BackgroundProblematic Internet Use (PIU) has been increasingly linked to suicidal behavior among adolescents, raising significant public health concerns, particularly in Chinese youth. This study aimed to systematically review and meta-analyze the correlation between PIU and suicidal behavior in Chinese adolescents to provide a clearer understanding of this association.MethodsA comprehensive search was conducted across seven databases up to July 1, 2024. Studies investigating the relationship between PIU and suicidal behavior among Chinese adolescents were included. A random-effects meta-analysis was employed to assess pooled effect sizes, with subgroup analyses conducted to explore potential moderators, such as geographic region, age, gender, assessment tools for PIU and suicidal ideation, and the presence of depression. Data analysis was performed using STATA software (version 16).ResultsThis meta-analysis, comprising 23 studies with 353,904 participants, identified significant associations between PIU and suicidal behavior among Chinese adolescents. PIU was associated with increased risks of suicidal ideation (OR = 1.72, 95% CI: 1.45, 2.03), suicidal plans (OR = 1.50, 95% CI: 1.02, 2.20), and suicidal attempts (OR = 1.48, 95% CI: 1.16, 1.89). Subgroup analyses indicated higher risks in specific groups: adolescents from Central China (OR = 1.84, 95% CI: 1.46, 2.32), college students (OR = 2.09, 95% CI: 1.66, 2.62). The risk of suicidal ideation was particularly elevated when depression was not controlled (OR = 1.86, 95% CI: 1.53, 2.25). These findings underscore the need for targeted interventions in vulnerable populations.ConclusionThis meta-analysis demonstrated significant associations between PIU and suicidal behaviors among Chinese adolescents. The findings emphasize the need for targeted interventions, particularly for adolescents from Central and Western China, college students, and those with untreated depression. Focused strategies are required to mitigate the risks associated with PIU and to effectively address suicidal behaviors in these high-risk populations.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024577593, identifier CRD42024577593.